Bloodkin - Atwater-Rhodes, Amelia (Atwater-Rhodes, Amelia. Maeve'ra, 2015)
When a shapeshifter/vampire nation is charged with a crime against Midnight that sixteen-year-old Kadee and her friend Vance played a hand in, Kadee feels compelled to return to the Shantel forest where she must confront her past and the decisions she's made in the pursuit of freedom.